Phytosome: Drug Delivery System for Polyphenolic Phytoconstituents: Phytosome - Anupama Singh,; Manjeet Singh,; Anil Bhandari,; Vikas Anand Saharan, (Iranian Journal of Pharmaceutical Sciences, 2011)
Several plant extracts and phytoconstituents, despite having excellent bioactivity in vitro, demonstrate less or no in vivo actions due to their poor lipid solubility or improper molecular size or destruction in gut. Drug delivery system for polyphenolic phytoconstituents (phytosomes) was prepared by complexing polyphenolic phyto phytoconstituents (phytosomes) was prepared by complexing polyphenolic phyto to each other on a molecular level. Bioavailability is enhanced due to their capacity to each other on a molecular level. Bioavailability is enhanced due to their capacity to each other on a molecular level. Bioavailability is enhanced due to their capacity have the capacity to deliver the standardized plant extracts and phytoconstituents through several routes of drug administration. Only a few natural drugs have been through several routes of drug administration. Only a few natural drugs have been applications of phytosomes numerous studies are undergoing and lots more is expected in the forthcoming years. The techniques used for such formulations are expected in the forthcoming years. The techniques used for such formulations are patentable and highly profitable.